THE CONTRIBUTIONS OF INVOLVING SPEAKING AND WRITING TEST IN NATIONAL EXAMINATION FOR SMA GRADUATION - Edi Suprayetno (LPPM STKIP AL MAKSUM, 2020)
This article is to analyze and observe how far is the contribution of writing and speaking test in National Examination and their implementation in the evaluation process during the process of learning. Based on the analysis it was found that the English subject tested in national examinations is dominantly measure the cognitive competence of the students because the content of the test question is only consist of listening and reading skill.There are six types of speaking: speaking confidently, informal conversation, interviews, in the work place, beauty pageants, general speaking skills, pantomime script, teacher, extemporaneous speaking.In mastering writing skill, students have to own much knowledge of grammar,knowing well about punctuation and sentence structure as well as rich vocabulary, correct spelling and formatting.In other words it could be said that it is very important to involve the speaking and writing test during the learning process to train students to be able to pass the English National Examination. By mastering speaking and writing skill SMA graduation will be able follow some sort of TOEFL or IELTS test to continue their studies abroad, or get a job at the company, it takes skill to speak and write in the interview test.